Thermodynamic and economic analysis of effect of heat accumulator volume on the specific cost of heat production in the gas-steam CHP plant. (1st September 2021) - Bartnik, Ryszard; Buryn, Zbigniew; Hnydiuk-Stefan, Anna
Abstract: The economic profitability of the operation of gas-steam CHP plants can be improved by using heat accumulators (HA) in them. Thanks to this at the peak of the needs of the National Power System (NPS), an additional amount of electricity will be produced, and in the condition of decreased demand in the NPS load valley, it will be reduced. The total production of electricity in the CHP plant will be at the same level as if there is no accumulator in it. In the article, an innovative methodology in a record with continuous time was used and technical with economic analysis was performed. The reduction of the specific cost of heat production in a CHP plants due to the use of a HA in it is significant and increases the economic profitability of its operation. The N P V a c c u value of the profit with the relatively high price of gas and the low price of electricity may exceed the value of the NPV profit. For the gas price 24 PLN/GJ and the electricity selling price of only 205 PLN/MWh, the profit for the CHP with a HA with V t max = 94 342 m 3 volume is 40 mln PLN greater than without using an accumulator. Graphical abstract: Image 1 Highlights: Economic profitability of the operation of gas-steam CHP with accumulator. Innovative methodology in a record with continuous time. The most economically advantageous volume of the heat accumulator. Economic indicators for heat production with the use of an accumulator. N P V max a c c u is achieved for V t max = 94 342 m 3 for the time of τ a = 12 h